THE STUDY OF THE EFFECT OF EVAPORATION ON THE QUALITY ACID WATER IN COAL MINES - Gabriella Zebua, Amelia
Mining activities will have an influence such as landscape changes. One adjustment in the landscape is the emergence of voids which will be used as openings filled with water or called pit lakes. Pit lake in open pit will be affected by precipitation and evaporation, which will cause an augementation and declining in the volume of water in the pit lake. This will alter the quality of water contained in the pit lake. The pit lake water will then be used for post-mining activities, so the pit lake water quality needs to be considered. Water quality can be determined by testing physical parameters and chemical parameters of water. Physical parameters measured in the study are volume, total dissolved solid (TDS), pH, electric conductivity (EC), and oxidation reduction potential (ORP). Water chemical parameters will present data in the form of cations, namely Na+, K+, Mg2+, NH4+, and anion content, namely F-, Cl-, SO42-, NO3-and metal content, namely chromium (Cr), nickel (Ni) , copper (Cu), zinc (Zn), arsenic (As), cadmium (Cd), iron (Fe), and manganese (Mn). The study was conducted to establish the effect of evaporation by ignoring precipitation. The study was divided into preliminary experiments and further experiments. Preliminary experiments were carried out with a cycle of 1 daily, 2 daily, and 3 daily. In the follow-up experiments a 2-day cycle is used and uses a sensor relative humidity, temperature, and pressure as an additional. Based on these studies, from the results of the physical parameters of the water test it was found that evaporation causes the sample volume to decrease, TDS, EC, and ORP to increase, and a decrease in pH. From the results attained from chemical parameter tests, it was found that evaporation caused the concentration of metals, anions, and cations to increase.